2012
DOI: 10.1002/sia.4925
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high wear resistance aluminium matrix nanoreinforced composite

Abstract: aBecause of the present economic conditions, the great energetic dependence on petroleum derivatives and the restrictive regulations of environmental pollution, development of new materials and processing methods has become a very important technological challenge. 7075 aluminium alloys (Al-Mg-Zn-Cu) have been widely used as structural materials in the aeronautics industry because of their attractive properties such as very low density and high specific strength, ductility, toughness and resistance to fatigue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…To optimize the dispersion of MWCNTs in composite powders, three mechanical ball milling strategies were compared in this study. These were carried out by following a cyclic operation mode in which the rotation speed was varied over 1 min cycles, maintaining the higher speed indicated in first place for 48 s and the second lower speed for the last 12 s. Previous research [33] showed that cyclic operation improves the efficiency of the process by avoiding the agglomeration and sticking of particles and reducing the milling time required to obtain a smaller-grained structure compared with conventional milling.…”
Section: Aa7075-mwcnt Composite Powder Preparationmentioning
confidence: 99%
“…To optimize the dispersion of MWCNTs in composite powders, three mechanical ball milling strategies were compared in this study. These were carried out by following a cyclic operation mode in which the rotation speed was varied over 1 min cycles, maintaining the higher speed indicated in first place for 48 s and the second lower speed for the last 12 s. Previous research [33] showed that cyclic operation improves the efficiency of the process by avoiding the agglomeration and sticking of particles and reducing the milling time required to obtain a smaller-grained structure compared with conventional milling.…”
Section: Aa7075-mwcnt Composite Powder Preparationmentioning
confidence: 99%
“…As a process controlling agent (PCA), amide micro-wax (0.5% by weight) (Licowax ® C micro powder, Clariant, Muttenz, Switzerland) was used to avoid cold welding between the powder particles, limiting agglomeration, and to prevent detrimental welding of the powder to the balls, the container walls and blades of the mill. A cyclic operation mode was performed for mixing AA7075 powders and the MWCNTs, alternating the rotary speed between 1300 (48 s) and 1000 rpm (12 s) in cycles of 1 min for 4 h. The cycle operation procedure has been proven to avoid sticking and agglomeration [26] and, compared to constant operation, has a significant influence on particle size reduction [27]. To study the variation of size and morphology of the composite powders and verify the dispersion of the nanotubes with time, samples were extracted after 2 and 4 h of HEBM.…”
Section: Aa7075-mwcnt Composites Preparationmentioning
confidence: 99%